The Influence of Organizational Social Support and Job Satisfaction on Work Stress in Polres Mojokerto: The Influence of Organizational Social Support and Job Satisfaction on Work Stress in Polres Mojokerto - Dhani, Jihan Zahrah Yasmin (Edusight International Journal of Multidisciplinary Studies, 2024)
This study aims to investigate the influence of organizational social support and job satisfaction on the level of work stress among police officers in Polres Mojokerto and to identify efforts that can be made to create a more supportive work environment and minimize the level of work stress. A quantitative research method was used with the population of police officers in Polres Mojokerto, and a sample of 30 individuals was selected using a simple random sampling method. The research findings indicate that organizational social support has a positive but not significant influence on police performance, while job satisfaction does not have a significant influence on performance. However, work stress has a significant negative influence on the performance of police officers. Factors such as anxiety, depression, and decreased trust in colleagues and superiors are identified as the main causes of work stress. The implications of these findings can be used to develop more effective human resource management strategies to reduce work stress and improve performance in the work environment of Polres Mojokerto.